Factors influencing e-wallet usage intentions among Gen Z and Millennials in Jabodetabek - setiawan, chandra; Purwanta, Sumedho Sappuriso Ti (International Journal of Scientific Research and Management (IJSRM), 2024)
This study explores the factors influencing the adoption of e-wallets in the Jakarta-Bogor-Depok-Tangerang-Bekasi (Jabodetabek) metropolitan region, Indonesia, among Generation Z and millennials. The research uses a quantitative approach and analyzes data from 136 participants using SEM-PLS. The study examines Perceived Usefulness, Ease of Use, Risk, Trust, Convenience, and Attitude toward the Service. The findings reveal that Perceived Ease of Use influences Usefulness rather than Attitude toward the Service. Perceived Risk influences Attitude toward the Service, and Trust is crucial. This research contributes significantly to the existing literature on e-wallets and digital payment technology in Indonesia, thus contributing to the growth of the country's digital economy. Providers should communicate transparently about security and improve accessibility to increase adoption rates.